Quality control of commercial cranberry products: HPTLC-densitometry a new deal. (April 2018) - Boudesocque-Delaye, Leslie; Lanoue, Arnaud; Dorat, Joëlle; Bruyère, Frank; Gueiffier, Alain; Enguehard-Gueiffier, Cécile
Abstract: A fast quality control protocol based on reference BL-DMAC assay and High-performance thin-layer chromatography (HPTLC)-Densitometry was optimized for routine quality control of cranberry ( Vaccinium macrocarpon ) products. The sample preparation appeared as a key step to ensure a relevant comparison of products quality and biological data. Sequential solid/liquid extractions were required to fully extract polyphenols, regardless the extraction solvent chosen. The HPTLC-densitometry herein protocol used epicatechin, PAC-A2 and PAC-B2 as quality markers and densitometric measurements at 200 nm. The PAC-A2 /Epicatechin ratio, obtained using HPTLC, appeared as an appropriate indicator of the quality of cranberry ingredient. Only two products, among the tested panel, exhibited a high quality cranberry-based ingredient using this criteria. UPLC-MS analyses coupled to multivariate analyses confirmed HPTLC-densitometry conclusions. This work highlighted the plural PAC composition of commercial products and the lack of standardization for cranberry-based products on the market, explaining the non-reproducibility of clinical trials. Highlights: HPTLC-densitometry protocol was optimized for low concentrated PACs products. Solid/liquid extraction appeared as a key step. This work highlighted the plural PAC composition of commercial products. UPLC-MS combined to multivariate analysis confirmed HPTLC data. PAC-A2 /Epicatechin ratio >2 is a pertinent quality indicator.